Pengaruh Sikap Kerendahan Hati dan Keteladanan Pemimpin Berdasarkan Yohanes 13:4-5 terhadap Pertumbuhan Gereja di Kota Batam - Saragi, Lydia Caesera; Sanjaya, Yudhy; Simanjuntak, Fredy (JURNAL TERUNA BHAKTI, 2022)
This study aimed to determine the effect of humility and exemplary of a leader based on John 13:4-5 on church growth in Batam. The respondents of this study were church members who had been active for more than one year. The data analysis technique used is multiple linear regression analysis. It used a quantitative method with primary data sources obtained directly by using a questionnaire. The results showed that partially the leader’s humility based on John 13:4-5 had a positive effect but not significant on church growth in Batam. Meanwhile, the exemplary of a leader based on John 13:4-5 had a positive and significant effect on church growth in Batam. Simultaneously, it was found that the humility and exemplary of a leader based on John 13:4-5 had a significant positive effect on church growth in Batam.